1993
DOI: 10.1051/jp4:1993383
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of coiled carbon fibers by the catalitic pyrolysis of acetylene

Abstract: Microcoiled carbon fibers were obtained by the Ni catalyzed pyrolysis of acetylene at 600-800°C.The presence of small amounts of a sulfur compound impurity was indispensable for the growth of the coiled carbon fibers in high yield with good reproducibility. The optimum growth temperature was 750°C irrespective of the kind of sulfur compounds used as the impurity. The optimum impurity gas flow rate was restricted to a very narrow range depending on the impurity type. The maximum yield (about 50 %) of the coiled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
1
3
1
Order By: Relevance
“…However, the number of MCCFs was found to be greater when grown in the presence of a Ni catalyst of the order of nanometers. This result is contradictory to the findings of Motojimia et al's study [8] in which they indicated that the maximum yield of MCCF was observed when the particle size of Ni was in the order of micrometers.…”
Section: Effect Of the Size Of The Ni Particlecontrasting
confidence: 98%
See 2 more Smart Citations
“…However, the number of MCCFs was found to be greater when grown in the presence of a Ni catalyst of the order of nanometers. This result is contradictory to the findings of Motojimia et al's study [8] in which they indicated that the maximum yield of MCCF was observed when the particle size of Ni was in the order of micrometers.…”
Section: Effect Of the Size Of The Ni Particlecontrasting
confidence: 98%
“…The size of the pitch of the coil decreased with increasing reaction time as shown in figures 8(a) and (b). Similar observations were reported elsewhere [8].…”
Section: Effect Of Reaction Temperaturesupporting
confidence: 93%
See 1 more Smart Citation
“…The addition of a small amount of sulfur impurity during the overall reaction has been noticed for one of the methods to enhance the carbon coils production yield and reproducibility (6). Motojima et al first reported the regularly microcoiled carbon fibers with high reproducibility by the catalytic pyrolysis of acetylene containing a small amount of sulfur impurity (7,8). Sulfur impurity was mostly incorporated in the form of hydrogen sulfide (H 2 S), carbon disulfide (CS 2 ), and thiophene (C 4 H 4 S) (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…We have obtained very regularly shaped micro-coiled carbon fibers (referred to as "carbon coils" hereafter). The carbon coils have a constant coil diameter of 1-10 m without coil gap when prepared by Ni-catalyzed pyrolysis of acetylene at 700-850 • C [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%